1996
DOI: 10.1007/bf00128958
|View full text |Cite
|
Sign up to set email alerts
|

Glioma invasionin vitro: regulation by matrix metalloprotease-2 and protein kinase C

Abstract: A hallmark of invasive tumors is their ability to effect degradation of the surrounding extracellular matrix (ECM) by the local production of proteolytic enzymes, such as the matrix metalloproteases (MMPs). In this paper, we demonstrate that the invasion of human gliomas is mediated by a 72 kDa MMP, referred to as MMP-2, and provide further evidence that the activity of MMP-2 is regulated by protein kinase C (PKC). The invasiveness of five human glioma cell lines (A172, U87, U118, U251, U563) was assessed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 50 publications
3
116
1
1
Order By: Relevance
“…39 Other studies have demonstrated that high levels of b1 integrin subunit are expressed in glioma cells, 31 and stimulation of the b1 integrin subunit increases the activation of MMP-2, which is the most crucial proteinase in the invasiveness of glioma cells. [40][41][42][43][44] We reported that cells migrating from malignant glioma spheroids can be stained with anti-MMP-2 antibody, despite poor staining of the spheroid itself. 30 We have not fully clarified the biologic mechanism through which glioma cell motility is suppressed by the downregulation of laminin a4 chain expression.…”
Section: Discussionmentioning
confidence: 99%
“…39 Other studies have demonstrated that high levels of b1 integrin subunit are expressed in glioma cells, 31 and stimulation of the b1 integrin subunit increases the activation of MMP-2, which is the most crucial proteinase in the invasiveness of glioma cells. [40][41][42][43][44] We reported that cells migrating from malignant glioma spheroids can be stained with anti-MMP-2 antibody, despite poor staining of the spheroid itself. 30 We have not fully clarified the biologic mechanism through which glioma cell motility is suppressed by the downregulation of laminin a4 chain expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, recombinant or over-expressed TIMP-4 had no effect on cellular viability and proliferation (as measured by 3 H-thymidine incorporation and MTT assays, data not shown), but substantially reduced the invasive capacity of glioma cells through Matrigel. Several MMPs have been linked with the invasive behaviour of malignant gliomas, including MMP-2, MMP-9 and MT1-MMP (Saxena et al, 1995;Sawaya et al, 1996;Uhm et al, 1996;Yamamoto et al, 1996;Deryugina et al, 1998;Lampert et al, 1998;Belien et al, 1999;Forsyth et al, 1999;Price et al, 1999;Raithatha et al, 2000). In particular there is growing evidence for involvement of several other members of the MT-MMP family including MT2-MMP (Nakada et al, 1999), MT5-MMP (Llano et al, 1999) and MT6-MMP (Velasco et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrocytes are frequently associated with glioma cells in the CNS (Le et al, 2003). Tumor-associated astrocytes have been demonstrated to mediate glioblastoma cell invasion via activation of proMMP2 (Le et al, 2003), a metalloproteinase that plays a critical role in glioma invasion (Uhm et al, 1996). Some reports have identified sonic hedgehog (SHH)-expressing reactive astrocytes to be highly concentrated in the perivascular regions of gliomas.…”
Section: Astrocytes In the Microenvironment Of Brain Tumorsmentioning
confidence: 99%
“…Co-cultures of brainderived human fibroblasts involving interactions with glioblastoma cells induced production and activation of matrix metalloproteinase MMP2, and its activators MT1-MMP and MT2-MMP (Sameshima et al, 2000). These metalloproteinases have all been shown to be involved in the progression of gliomas (Belien et al, 1999;Sawaya et al, 1996;Uhm et al, 1996).…”
Section: Fibroblasts In the Brain Tumor Microenvironmentmentioning
confidence: 99%